Acute responses of comprehensive gonadosteroids and corticosteroids to resistance exercise before and after 10 weeks of supervised strength training. Issue 3 (3rd February 2020) - Walker, Simon; Häkkinen, Keijo; Newton, Robert U.; Markworth, James F.; Pundir, Shikha; Haff, Guy G.; Cameron‐Smith, David; Blazevich, Anthony J.
Abstract : New Findings: What is the central question of this study? Although acute responses of the principal gonadosteroid and corticosteroid hormones to resistance exercise are well documented, there is no information regarding how the key lower‐concentration intermediary hormones respond and potentially influence these hormonal pathways. What is the main finding and its importance? This study provides evidence for cascading conversions of some gonadosteroids, and the data suggest that the testosterone concentration increases independently of these hormones. These findings challenge future studies to determine the exact physiological roles of the lower‐concentration gonadosteroids and corticosteroids during and immediately after resistance exercise. Abstract: Resistance training is a potent stimulus for muscle growth, and steroid hormones are known to play a role in this adaptation. However, very little is known about the acute exercise‐induced gonadosteroid and corticosteroid hormone responses, including those of key lower‐concentration intermediate hormones. The present study determined the acute responses of these steroid hormone families using quantitative ultra‐high performance liquid chromatography tandem mass spectrometry after resistance exercise in strength‐trained men. Venous and fingertip blood samples were obtained pre‐, mid‐, 5 min post‐ and 15 min post‐resistance exercise, both before and after 10 weeks of supervised resistance training. The experimental resistance exercise sessions consisted of three sets of 10 repetitions of bilateral leg‐press exercise and three sets of 10 repetitions of unilateral knee‐extension exercise, with 2 and 1 min recovery between sets, respectively. Statistically significant ( P < 0.05) increases in the concentration of hormones in the gonadosteroid [including dehydroepiandrosterone (DHEA), androstenedione, testosterone and estrone] and the corticosteroid (including cortisol, corticosterone and cortisone) families were demonstrated after both experimental resistance exercise sessions, irrespective of training status. Correlation analyses revealed relationships between the following hormones: (i) DHEA and androstenedione; (ii) DHEA and cortisol; (iii) androstenedione and estrone; and (iv) 11‐deoxycortisol and cortisol. Testosterone appears to increase acutely and independently of other intermediary hormones after resistance exercise. In conclusion, lower‐concentration intermediary gonadosteroids (e.g. estrone) and corticosteroids (e.g. corticosterone) respond robustly to resistance exercise in strength‐trained men, although it seems that testosterone concentrations are regulated by factors other than the availability of precursor hormones and changes in plasma volume. Abstract :